Noodle and the no bones day - Graziano, Jonathan (Margaret K. McElderry Books, an imprint of Simon & Schuster Children's Publishing Division, 2022)
Noodle is an active old pug, but one day when his favorite human lifts him up Noodle just flops over like he as no bones and Jonathan soon learns that not every day can be a Bones Day, and sometimes a No Bones Day is exactly what you need to get through the week.